Strength and Thermal Conductivity of Hydrated Solidified Materials Made from Wastepaper Sludge Ash and By-products - Naoki KINOSHITA; Hideaki YASUHARA (Journal of MMIJ, 2022)
The purpose of this study is to expand the application of wastepaper sludge ash (WPSA) as a construction material. The strength and thermal conductivity of WPSA solidified by hydration reaction were investigated for use as a ground improvement solidifier and civil engineering material. The mixture of fly ash, silica fume, gypsum, and ordinary Portland cement was also investigated. The effect of the mix proportion and the amount of the powder mixture on the strength was investigated, and the strength development was discussed based on the XRD and SEM-EDX results. The experimental results showed that the uniaxial compressive strength of mortar specimens with a water-powder ratio of 1.0 was 5 MPa to 9 MPa at 28 days of age. The strength of the mortar specimens decreased with the addition of fly ash but increased with the addition of by-products such as silica fume. The strength of the solidified material using WPSA was lower than that of the existing solidified materials. The strength of the solidified material made of WPSA was developed due to the formation of albite by hydration reaction, recrystallization of WPSA, and pozzolanic reaction with fly ash and silica fume. Then, the reflectance and thermal conductivity of the solidified material were measured, and the thermal conductivity was examined by the heat transfer experiments. The thermal diffusivity of the solidified material was also estimated by analyzing the experimental results. It was confirmed that the reflectance of WPSA was higher than that of ordinary Portland cement. In addition, the re-incineration of WPSA showed higher reflectivity. The thermal conductivity of the WPSA paste specimens was smaller than that of cement mortar and larger than that of gypsum. The results of the heat transfer experiments suggest that the thermal insulation property of the re-incinerated WPSA is improved.